Dasar Pertimbangan Hakim Menjatuhkan Pemidanaan kepada Pelaku yang Melakukan Penampungan untuk Eksploitasi Orang di Wilayah Negara Republik Indonesia - Dahris Siregar; Yaniman Gulo; Yurmanius Laia; Ariston Halawa; Niamulago Laia; Yohanes Herman Buulolo; Hiraukan Zebua; Korintus Laia; Senius Zega; Angoligo Laia (Inovasi Pratama Internasional. Ltd, 2023)
Exploitation is an act with or without the consent of the victim which includes but is not limited to prostitution, forced labor or services, slavery or practices similar to slavery, oppression, extortion, use of physical, sexual, reproductive organs, or unlawfully transferring body or tissue or utilizing power or ability of a person by another party to gain material or immaterial benefits. The criminal act of trafficking in persons is any action or series that fulfills the elements of a criminal act as stipulated in Law No. 21 of 2007 concerning the eradication of the crime of trafficking in persons. Human trafficking (trafficking) has long occurred on this earth and is an act that is contrary to human dignity. This is a violation of human rights, rights and human dignity which are protected under Pancasila and the 1945 Constitution. In the past, trafficking in persons was only seen as forcible transfer abroad for the purpose of prostitution, illegal forced labor that lasted for a long time. TPTPPO can be committed by individuals, groups, corporations and sometimes by family (parents/siblings), relatives, friends or neighbors of the victim. Victims of TIP are generally women and children, this is possible because they are very vulnerable and considered weak (physical and psychological) so that traffickers are very easy to deceive. Victims often receive cruel treatment, suffering, not even a few who experience violence and threats of violence. They are trapped in a network of powerlessness or by trapping, deceiving, persuading, with the lure and promises of success stories, economic benefits, or providing loans which in the end is debt bondage.